The Utilization of Technology in the Production of Trichocompost Fertilizer and its Subsequent Application to Chrysanthemum Plants at the Pudak Lestari Agro Ornamental Plant Farmer Group - A. A. S. Putri Risa Andriani; Nicolas, Amelia R; Situmeang , Yohanes Parlindungan; Suaria, I Nengah; Suarta, Made; Sulistiawati, Ni Putu Anom; Sudewa, Ketut Agung; Astiari, Ni Komang Alit (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The ornamental plant farmer group Agro Pudak Lestari has long cultivated chrysanthemums. In the cultivation of chrysanthemums, the Agro Pudak Lestari farmer group experienced several obstacles, namely yields that did not meet market criteria caused by white rust disease. Antagonistic microorganisms (Trichoderma sp.) effectively control white rust disease. White rust disease is a soil infectious disease so countermeasures are carried out by making compost containing the biological agent Trchoderma (Trichocompost fertilizer). From the survey results, the results of flower damage due to rust disease reached 80%. Furthermore, after the application of Trichocompost fertilizer treatment, it suppressed rust disease by 56.4%. From this activity, it was able to reduce yield losses by 23.4% and increase farmers' income by 28.2%. The use of Trichocompost fertilizer can overcome white rust disease in chrysanthemum plants so it can increase farmer productivity.